2015
DOI: 10.1111/gcb.12894
|View full text |Cite
|
Sign up to set email alerts
|

Evidence of climate‐driven ecosystem reorganization in the Gulf of Mexico

Abstract: The Gulf of Mexico is one of the most ecologically and economically valuable marine ecosystems in the world and is affected by a variety of natural and anthropogenic phenomena including climate, hurricanes, coastal development, agricultural runoff, oil spills, and fishing. These complex and interacting stressors, together with the highly dynamic nature of this ecosystem, present challenges for the effective management of its resources. We analyze a compilation of over 100 indicators representing physical, biol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
61
2

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 50 publications
(65 citation statements)
references
References 64 publications
(67 reference statements)
2
61
2
Order By: Relevance
“…Climate change, invasive species, storms, and water quality degradation are potential threats (ONMS 2008;Nuttall et al 2014). As the Gulf of Mexico ecosystem continues to change (Karnauskas et al 2015), ongoing monitoring will be critical to document ecosystem variation. The relatively high coral cover since the beginning of the monitoring program make EFGB and WGB ideal for protection and conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Climate change, invasive species, storms, and water quality degradation are potential threats (ONMS 2008;Nuttall et al 2014). As the Gulf of Mexico ecosystem continues to change (Karnauskas et al 2015), ongoing monitoring will be critical to document ecosystem variation. The relatively high coral cover since the beginning of the monitoring program make EFGB and WGB ideal for protection and conservation.…”
Section: Resultsmentioning
confidence: 99%
“…Rather, effects of climatic drivers within the optimal DFA models were survey specific and likely indicative of localized distributional reorganization, while the estimated DFA trends reflect underlying patterns in relative abundance over broad geographic scales. These regional distributional changes due to climatic forcing may be the mechanism underlying local ecosystem reorganization noted by several studies (Stenseth et al ., and references therein; Collie et al ., ; Nye et al ., , ; Karnauskas et al ., ).…”
Section: Discussionmentioning
confidence: 99%
“…The NAO, which is a measure of pressure difference over the North Atlantic Ocean, and AMO, which encompasses basin‐wide sea surface temperature, circulation patterns and sea level pressure, were selected as environmental drivers because they directly impact climate patterns and have been shown to affect fish survival and ecosystem organization through bottom‐up control in the south‐east United States. Atlantic coast and Gulf of Mexico (Stenseth et al ., and references therein; Collie, Wood, & Jeffries, ; Nye, Link, Hare, & Overholtz, ; Nye et al ., ; Karnauskas et al ., ). Annually averaged SST was included because several studies have shown that shark movement is influenced by temperature patterns (e.g.…”
Section: Methodsmentioning
confidence: 99%
“…Multi‐disciplinary, ecosystem‐based approaches have emerged as particularly promising novel frameworks, resulting in significant advances in both research and management applications. For instance, local societal and ecological changes have been linked to global climate change (Karnauskas et al, ), biophysical modelling has been integrated with population genetics (Selkoe et al, ), ecosystem service ideas have been expanded to include relational values (Chan et al, ), and fisheries sustainability has been added to biodiversity in considering the effectiveness of marine protected areas (Krueck et al, ). Furthermore, recent ideas promote decision‐making based upon expected future ecosystem states, as opposed to past baselines, to increase the efficacy of future management strategies (Rogers et al, ).…”
Section: Learning From Previous Successesmentioning
confidence: 99%